Noncirrhotic Portal Vein Thrombosis Presenting with Hepatic Encephalopathy Due to Polycythemia Vera and MRI Findings - Burcu GÖKÇE ÇOKAL; Tahir KURTULUŞ YOLDAŞ; Selda KESKİN GÜLER; Murat KEKİLLİ; Faruk PİRİNÇCİOĞLU; Hafize NALAN GÜNEŞ (Tehran University of Medical Sciences, 2017)
Noncirrhotic Portal Vein Thrombosis Presenting with Hepatic Encephalopathy Due to Polycythemia Vera and MRI Findings